2019
DOI: 10.1111/geer.12156
|View full text |Cite
|
Sign up to set email alerts
|

Tax Composition and Growth: A Broad Cross-country Perspective

Abstract: We investigate how changes in the composition of tax revenue affect long‐run growth in a broad cross‐section of countries. To do this, we construct a new dataset that covers 70 countries (23 high‐, 23 middle‐ and 24 low‐income countries), with at least 20 years of observations during the period 1970–2009. In the context of revenue‐neutral reallocations, we find that increasing consumption and property taxes while reducing income taxes boosts long‐term growth. Among income taxes, we find that social security co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
19
2
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 42 publications
4
19
2
1
Order By: Relevance
“…This is in accordance with the theoretical model, in which the various variables in the transition-to-the-steady-state (transitional growth) equation reflect accumulation / growth rates in the capital stocks and public finance variable 3. Through a Monte-Carlo simulation study,Blundell and Bond (1998) show that when the series are highly persistent (close to a random walk) in short panels, the system GMM estimator is more robust.…”
supporting
confidence: 82%
See 1 more Smart Citation
“…This is in accordance with the theoretical model, in which the various variables in the transition-to-the-steady-state (transitional growth) equation reflect accumulation / growth rates in the capital stocks and public finance variable 3. Through a Monte-Carlo simulation study,Blundell and Bond (1998) show that when the series are highly persistent (close to a random walk) in short panels, the system GMM estimator is more robust.…”
supporting
confidence: 82%
“…In such a situation, it is suggested that an alternative estimator (system GMM) should be employed, which, in addition to lagged levels as instruments for variables in first differences, uses lagged first differences as instruments for variables in levels (Arellano & Bover, 1995;Blundell and Bond, 1998). 3 Since in our panel, the time dimension is rather long and the variables are not highly persistent, the above mentioned issues do not arise. In any case, we have estimated equation (3) with both, the first-differenced GMM and the system GMM estimator.…”
Section: Model Specificationmentioning
confidence: 99%
“…Taxes should therefore be simple, tax bases should be as broad as possible (Mirrlees et al 2010), and rates should be the lowest 7 2 concepTual framework possible to collect a given amount of revenue. Overall, the most conclusive empirical evidence for advanced and developing countries suggests that taxes on income are particularly harmful to growth, while taxes on consumption and property are less so (Arnold 2008;Arnold et al 2011;Acosta-Ormaechea and Yoo 2012).…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…A number of studies in this area have investigated the trends in taxation of various countries at different stages of their economic growth using the ratio of total tax revenues to GDP as a proxy for taxing power, indicating positive relationship between rate of economic growth and tax structure. In particular, the first testable hypothesis of this chapter --that as economies grow, tax revenue relative to GDP continues to rise --is echoed in the earlier works of scholars (Abizadeh and Yousefi, 1996;Abizadeh and Grey, 1985;Abizadeh, 1979;Abizadeh, 1988;Acosta-Ormaechea and Yoo, 2012;Bahl, 1971;Easterly and Rebello, 1993;Ram, 1987). As for the second hypothesis on why tax structures change systematically with economic growth (the change in income levels), a number of studies have relied upon empirical models to elaborate on this subject (e.g.…”
Section: Development Context and Changes In Structure Of Taxation In mentioning
confidence: 73%
“…Value-added tax (VAT) and sales taxes rise with income too, but differences among income groups for these taxes are rather less substantial compared to the PIT and SSC. Collection of trade taxes drop with the level of development (Baunsgaard and Keen, 2010;Acosta-Ormaechea and Yoo, 2012). As for corporate income taxes (CIT) and property taxes, they increase with income, but not to the extent of the PIT and SSC growth with income level.…”
Section: Review Of Trends In Tax Revenue and Changes In Tax Structurementioning
confidence: 99%